Growth Performance and In vivo Nutrients Digestibility of Growing Yankasa Ram Lambs Fed Diets Containing Graded Levels of Sesame Residue - Adeola, Emmanuel A.; Garba, Yusuf; Baba, Mohammed (Nexus Academic Publishers, 2021)
The study was carried out to evaluate the effect of including sesame residue (SR) in the diets of Yankasa ram lambs on feed intake, body weight gain, and nutrients digestibility. Twelve Yankasa ram lambs (initial body weight of 20.08 ± 3.08kg) were allotted to three dietary treatments containing 0, 20 and 30% SR (A, B and C) respectively. A completely randomized design was used for the study which lasted twelve weeks. The results revealed that animals fed 30% inclusion level had higher dry matter, nitrogen free extract and ether extract intakes, which varied among the treatments. Organic matter, neutral detergent fiber and acid detergent fiber digestibilities were higher for the lambs fed 0% SR. Inclusion of sesame residue up to 30% in the diet of growing Yankasa lambs improved nutrients intake without adverse effects on growth performance. It is thus recommended that sesame residue could be incorporated in the diets of growing Yankasa lambs at 30% inclusion level for reduced feed cost in Sudan Savanna agro-ecological zone of Nigeria.
J. Anim. Health Prod. 9(2): 107-111.
Keywords: Sesame residue; Growth performance; Nutrients digestibility; Proximate composition; Lamb; CDA; Bayero University, Kano; Nigeria